Hepatorenal dysfunction in patients with chronic thromboembolic pulmonary hypertension - Yogeswaran, Athiththan; Zedler, Daniel; Richter, Manuel J.; Steinke, Sonja; Rako, Zvonimir A.; Kremer, Nils C.; Grimminger, Friedrich; Seeger, Werner; Ghofrani, Hossein Ardeschir; Gall, Henning; Tello, Khodr (Frontiers in Medicine, 2023)
Background Cardiac interactions with organs such as the liver or kidneys have been described in different cardiovascular diseases. However, the clinical relevance of hepatorenal dysfunction in chronic thromboembolic pulmonary hypertension (CTEPH) remains unclear. We determined the association of hepatorenal dysfunction (measured using the Model for End-stage Liver Disease Sodium [MELDNa] score) with right heart function and survival in patients with CTEPH. Methods We analyzed all patients with CTEPH in the Giessen Pulmonary Hypertension Registry who had available MELDNa scores and were not taking vitamin K antagonists. The MELDNa score was calculated as MELD score − serum Na − (0.025 * MELD score * (140 − serum Na)) + 140; the MELD score was calculated as 10*(0.957*ln(creatinine)+0.378*ln(bilirubin)+1.12*ln(International Normalized Ratio))+6.43. Results Seventy-two patients were included (74% female; median [Q1, Q3] MELDNa: 9 [6, 11]). MELDNa correlated well with right atrial and ventricular function and pulmonary hemodynamics. Forward regression analysis revealed that hepatorenal dysfunction mainly depends on right atrial strain and tricuspid regurgitation, but not right ventricular systolic dysfunction. Hepatorenal dysfunction predicted mortality at baseline and follow-up (adjusted hazard ratios [95% confidence intervals] per unit increase of MELDNa: 1.6 [1.1, 2.4] and 1.8 [1.1, 2.9], respectively). Changes in hepatorenal function also predicted mortality. Conclusion Hepatorenal dysfunction in CTEPH is primarily associated with venous congestion rather than cardiac forward failure. As a surrogate parameter for hepatorenal dysfunction, MELDNa is a simple method to identify at-risk patients at baseline and follow-up.